Development Career Guidance Module Based on Adaptability to Enhance High School Students' Career Readiness - Hulukati, Wenny; Rahim, Maryam; Lakadjo, Mohamad Awal (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to develop a career guidance module based on career adaptability to assist high school students in recognizing their potential, understanding career options, and overcoming decision-making ambivalence. This research uses the Research and Development (R&D) method with the Sugiyono development model consisting of seven steps out of the ten main stages: (1) potential and problems identification, (2) data collection, (3) product design, (4) design validation, (5) product revision, (6) product trials, and (7) product revision. Data were collected using questionnaires, including: (1) expert validation questionnaires (experts in guidance and counseling, Indonesian language, and media design) and (2) small group trial questionnaires (teachers and students). Small group trials were conducted at State Senior High School 2, Gorontalo City. Quantitative analysis was used to assess the module’s validity, and open-ended feedback provided insights into the strengths and weaknesses of the module during small group trials. Results indicate that the module has a high level of validity and effectively supports more systematic and relevant career guidance services. The module offers a practical solution to enhancing students’ self-efficacy in navigating career dynamics, planning their future, and supporting the implementation of the